Comparability of Weighed Dietary Records and a Self-Administered Diet History Questionnaire for Estimating Monetary Cost of Dietary Energy - Kentaro Murakami; Satoshi Sasaki; Yoshiko Takahashi; Hitomi Okubo; Naoko Hirota; Akiko Notsu; Mitsuru Fukui; Chigusa Date (SAGE Publishing, 2008)
An increasing number of studies have estimated monetary diet cost using various dietary assessment methods, based on databases on retail food prices, for investigating its association with dietary intake and health outcomes. However, information regarding the comparability of monetary diet cost across dietary assessment methods is absolutely lacking. This study compared monetary cost of dietary energy estimated from weighed dietary records (DRs) with that estimated from a self-administered diet history questionnaire (DHQ). The subjects were 92 Japanese women aged 31-69 years and 92 Japanese men aged 32-76 years. The DHQ (assessing diet during the preceding month) and 4-day DRs (one weekend day and three weekdays) were completed in each season over a 1-year period (DHQs1-4 and DRs1-4, respectively). An additional DHQ was completed at one year after completing DHQ1 (DHQ5). Monetary cost of dietary energy (Japanese yen/4184 kJ) was calculated using food intake information derived from each dietary assessment method, based on retail food prices. Pearson correlation between the mean of DRs1-4 and mean of DHQs1-4 was 0.64 for women and 0.69 for men. Pearson correlation between the mean of DRs1-4 and DHQ1 was 0.60 for women and 0.52 for men, while intraclass correlation between DHQ1 and DHQ5 was 0.64 for women and 0.51 for men. These data indicate reasonable comparability of monetary cost of dietary energy across DR and a DHQ as well as usefulness of a single administration of the DHQ for estimating monetary cost of dietary energy.